Answer:
Step-by-step explanation:
We have
[tex]S_n =\frac{n(n+1)}{2} \\C_n = (\frac{n(n+1)}{2})^2[/tex]
To prove that [tex]C_n = S_n^2[/tex] by induction
Let P(n) be that statement for n
n=1 gives left side =1 =right side
True for n=1
Assume that P(k) is true
i.e. [tex]S_k^2 = C_k[/tex]
We have to prove P(k+1) is true assuming P(k)
LHS of [tex]P(k+1) = (\frac{(k+1)(k+2)}{2} )^2[/tex]
RHS = [tex]C_k+(k+1)^3\\= (\frac{k(k+1)}{2} )^2+(k+1)^3[/tex]
since by adding last term with Ck gives the sum
For simplification take (k+1) square outside
RHS = [tex]\frac{(k+1)^2}{4} [k^2+4(k+1)]\\=\frac{(k+1)^2}{4}(k+2)^2\\=LHS[/tex]
Thus proved by mathematical induction